Evaluating Analytic Rubric Quality for Assessing Pre-service Biology Teachers' Creative Thinking Skills - Pada, Andi Ulfa Tenri; Yulisman, Hendra; Melvina (Universitas Negeri Semarang, 2025)
This study validates an analytic rubric designed to assess divergent thinking as a core dimension of pre-service biology teachers' creative thinking. The research addressed the absence of psychometrically sound assessment tools in Indonesian biology education, where creativity remains underdeveloped despite policy mandates, such as Kurikulum Merdeka, and international benchmarks, like PISA 2022. The study pursued two objectives: (1) theoretical validation of the rubric through expert judgment and inter-rater reliability, and (2) empirical validation through exploratory and confirmatory factor analyses. Eight subject-matter experts evaluated the rubric's descriptors, and 218 pre-service biology teachers completed divergent-thinking tasks based on human physiology scenarios. Content validity was calculated using Aiken's V, inter-rater agreement with Kendall's W, and construct validity and reliability through EFA and CFA. Findings indicated strong content validity (Aiken's V = 0.78–1.00) and fair to good inter-rater reliability (Kendall's W = 0.50–0.79). Factor analyses confirmed a unidimensional structure, with CFA demonstrating good model fit (RMSEA = 0.04; CFI = 0.97). All factor loadings exceeded 0.30, and composite reliability was ≥0.70 for three dimensions, though solution variety was marginally reliable. Notably, feasibility emerged as more stable than variety, suggesting that appropriateness is a stronger indicator of creativity in applied STEM contexts. The validated rubric provides theoretical insights into the structure of divergent thinking and practical tools for formative assessment in biology education. Future studies should extend validation across institutions, examine measurement invariance, and explore predictive validity to ensure broader applicability.